1999
DOI: 10.2169/internalmedicine.38.461
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Changes of the Nonstructural 5A GENE by Prolonged Interferon Therapy for Patients with Hepatitis C Virus genotype 1b and a High Level of Serum HCV-RNA.

Abstract: Object: The aim of this study was to examine the efficacy and the changes of amino acid sequences of the interferon sensitivity-determining region (ISDR) by prolonged interferon (IFN) treatment in patients who have serum hepatitis C virus (HCV)-genotype lb and a high level of serum HCV-RNA. Methods: Inclusion criteria were biopsy-proven chronic hepatitis, positive HCV-RNA,and an abnormal serum aminotransferase level. Twenty-five patients received 6 MU of natural IFN-oc daily for 8 weeks, followed by three time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…This sequence has been termed the interferon sensitivity-determining region (ISDR). These results were then confirmed by other Japanese studies [11][12][13][14][15] , but were never in accordance with most Western European [16][17][18][19][20] and American studies [21][22][23] , in which most of the ISDR sequences harbored an intermediate profile.…”
Section: Introductionsupporting
confidence: 65%
“…This sequence has been termed the interferon sensitivity-determining region (ISDR). These results were then confirmed by other Japanese studies [11][12][13][14][15] , but were never in accordance with most Western European [16][17][18][19][20] and American studies [21][22][23] , in which most of the ISDR sequences harbored an intermediate profile.…”
Section: Introductionsupporting
confidence: 65%
“…Of these 11 substitutions, only R2234Q is unique to IFN-sensitive ISDRs. The R2234Q substitution is also lacking in the ISDR sequences of all other IFN-resistant viruses published to date but not included in the database [Rispeter et al, 1998;Ibarrola et al, 1999;Mihm et al, 1999;Arase et al, 1999;Sakuma et al, 1999]. The observation that substitutions in IFN-sensitive viruses are not less conservative than substitutions in the IFN-resistant viruses suggests that the general integrity of the NS5A protein is maintained in IFNsensitive viruses.…”
Section: Analysis Of Individual Substitutions In the Isdrmentioning
confidence: 99%
“…Of the 25 studies that have published ISDR sequences from IFN resistant and IFNsensitive viruses, nine support the Enomoto model and conclude that, at the 5% significance level, the data provide sufficient evidence that IFN-response and substitutions in the ISDR are dependent [Enomoto et al, 1995[Enomoto et al, , 1996Chayama et al, 1997;Kurosaki et al, 1997;Fukuda et al, 1998;Saiz et al, 1998;Murashima et al, 1999;Sarrazin et al 1999;Sakuma et al, 1999]. The other 16 studies were unable to conclude that there is a correlation [Hofgartner et al, 1997;Khorsi et al, 1997;Squadrito et al, 1997;Zeuzem et al, 1997;Duverlie et al, 1998;Franguel et al, 1998;Odeberg et al, 1998;Pawlotsky et al, 1998;Polyak et al, 1998;Rispeter et al, 1998;Chung et al, 1999;Sarrazin et al 1999;Squadrito et al, 1999;Ibarrola et al, 1999;Mihm et al, 1999;Arase et al, 1999].…”
Section: Introductionmentioning
confidence: 98%
“…To enhance the response rate, prolonged IFN therapy, [12][13][14] or combination therapy with other drugs (e.g., ribavirin) has been reported recently. 6,7 However, irrespective of the treatment strategy, the viral clearance rate remained at 20%-30%, at most, in patients with HCVgenotype 1b and an HCV-RNA level of more than 1 Meq/ml.…”
Section: Factors Determining Cr By Logistic Regression Analysismentioning
confidence: 99%
“…To reduce the relapse rate and improve the response rate, various approaches have been used, including the administration of IFN with other agents, [5][6][7][8][9][10] and prolongation of and/or higher dose/ higher frequency of IFN therapy. [11][12][13][14] For the treatment of chronic hepatitis B, several studies have suggested that the serum level of hepatitis B virus decreases after acute exacerbation. 15,16 Similarly, in patients with chronic hepatitis C, the serum HCV-RNA level may decrease at the recovery stage of alanine aminotransferase (ALT) relapse.…”
Section: Introductionmentioning
confidence: 99%